Analisis Kinerja Brushless Motor Tipe MR 2205-2300 KV Menggunakan Metode Eksperimen dengan Variasi Propeller - Erwan Eko Prasetiyo; Wahyuni Fajar Arum (Fakultas Teknik Elektro - Universitas Sultan Ageng Tirtayasa, 2020)
Unmanned Aerial Vehicle (UAV) technology is now increasingly used and continues to be developed. In addition to developing more sophisticated UAV technology, it is also necessary to develop drones that are efficient in consuming energy. The purpose of this study was to determine the performance of the brushless motor type MR 2205-2300 KV with three different propeller variations, namely two blades of type 5152, three blades of type 5055, and four blades of type 5040. The performance of the brushless motor is seen based on power consumption, the amount of thrust produced, and the ratio of the ratio between the thrust produced to the power consumed. So that it can be seen the amount of power consumed by a brushless motor to produce thrust per gram. The performance of the brushless motor type MR 2205-2300 KV with a variation of the propeller requires relatively the same power, namely an average of 29.3 Watts to 29.9 Watts, while the resulting thrust value is different. The test results show that the 2 blades type 5152 propeller produces a thrust of 15.20 grams with a ratio of 1.81. The 3 blades propeller type 5055 produces a thrust of 141.28 grams with a ratio of 0.20. The 4 blades propeller type 5040 produces a thrust of 138.12 grams with a ratio of 0.21. From the test results with the three types of propellers, the MR 2205-2300 KV brushless motor consumes the most efficient power when paired with the 3 blades type 5055 propeller.